Review of External Audit Practices at PT Indofood Sukses Makmur Tbk - Fachri Aditya; Amri Amrulloh; Eka Noviana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study explores external audit practices in manufacturing companies. This article aims to examine external audit practices at PT Indofood, one of the largest food and beverage companies in Indonesia. The primary focus is on the audit procedures used and compli- ance with applicable audit standards. By using literature analysis and secondary data from various journals and PT Indofood's annual financial reports, this research provides in-depth insight into the effectiveness of external audits in increasing company transparency and accountability. The existing findings show that PT Indofood has carried out an external audit of their consolidated reports in accordance with applicable regulations. This finding underlines that no problems have occurred with external audit practices within PT Indofood so far.